Evaluation of urban resilience level and analysis of obstacle factors: A case study of Hunan Province, China - Chen, Na; Guo, Hongxia; Xiang, Hui (Frontiers in Earth Science, 2023)
Resilient city is an ideal goal and model of urban development proposed in response to today’s complex and dynamic environmental changes. In this study, a resilient city evaluation framework of “social resilience-economic resilience-urban infrastructure and service-urban governance” was built upon the multi-dimensionality of the urban system; the entropy weight method was used to measure the level of urban resilience in Hunan Province while an obstacle degree model was used to identify any obstacle factor restricting to the development of resilience. The results show that the level of urban resilience in Hunan Province has grown slowly over the past 10 years, and there is an obvious regional difference in it. There are more and more highly resilient cities, but medium/low-resilience cities still dominate the province, forming a spatial process of evolution from “medium/high-level dispersion” to “medium/high-level aggregation” in the Changsha-Zhuzhou-Xiangtan Urban Agglomeration. The level of urban resilience is predominantly hindered by the social and economic systems; at the index layer, most obstacle factors are moving from the economic system to the social-economic-urban infrastructure and service system.